Wide field imaging biomarkers: A different perspective - Sakshi Shiromani; Niveditha Pattathil; Elham Sadeghi; Netan Choudhry; Jay Chhablani (Taiwan Journal of Ophthalmology)
Wide field retinal imaging has emerged as a transformative technology over the last few decades, revolutionizing our ability to visualize the intricate landscape of the retina. By capturing expansive retinal areas, these techniques offer a panoramic view going beyond traditional imaging methods. In this review, we explore the significance of retinal imaging-based biomarkers to help diagnose ocular and systemic conditions. We discuss quantitative biomarkers, including ischemic index, nonperfusion area and more, and their application in diabetic retinopathy, central retinal vein occlusion, neurodegenerative diseases, and more. In addition, we outline qualitative biomarkers such as choroidal venous hyperpermeability and intervortex anastomoses. The role of wide field fundus autofluorescence in assessing hereditary retinal diseases is also emphasized. Standardized imaging procedures, professional collaboration, and validation across a range of clinical circumstances are necessary for the effective use of these biomarkers. They have the potential to transform disease identification, risk assessment, and customize therapy.